A Study on the Elemental Composition of Chinese Mise Type Wares from Different Periods and Kilns. (29th January 2018) - Sun, H. Y.; Li, L.; Zheng, J. M.; Yan, L. T.; Huang, Y.; Feng, X. Q.
Abstract : A large number of porcelain shards were unearthed at the Hehuaxin and Silongkou kilns around the Shanglin Lake, Ningbo, China, some of which had clear stratification to enable the determination of the date of firing. With the purpose of studying the elemental composition in different cultural periods and between kilns, the chemical compositions of 43 typical shards from these two kilns were determined by energy‐dispersive X‐ray fluorescence (EDXRF). The results show that the mean contents of K2 O, CaO and MnO in the glaze fluctuate in different cultural periods at the Hehuaxin kiln, but not systematically. Principal component analysis (PCA) indicates that samples from the Five Dynasties and the Northern Song dynasty are similar to each other. This shows continuity in the raw materials and firing technology between the two dynasties. Comparing the mise type wares from the Hehuaxin and Silongkou kilns in the Northern Song dynasty, we found that MnO and ZrO2 in the glaze can be used as fingerprinting elements to distinguish between samples from these two sites. In spite of this, their chemical compositions are broadly similar. Thus, perhaps, their chemical compositions can be taken as typical for those of the mise type wares produced around the Shanglin Lake.